The Influence Of Leadership And Organizational Culture On Employee Work Effectiveness At The Gowa Regency Samsat Office - Finni Alfiani; Sri Andayaningsih; Muhammad Akib (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study investigates the influence of leadership and organizational culture on employee work effectiveness at the Gowa Regency SAMSAT Office, Indonesia. Human resources are considered the most strategic asset in public service institutions, where leadership and organizational culture are two critical determinants of performance. A quantitative research design was employed using a saturated sampling technique, with the entire population of 43 employees selected as respondents. Data were collected through structured questionnaires, observations, and documentation, and analyzed using multiple linear regression with the SPSS 27 software. The validity and reliability tests confirmed that the research instruments met the required standards. The results revealed that leadership had a positive and significant effect on employee work effectiveness (β = 0.187; p = 0.025), indicating that effective leadership styles enhance employee productivity, communication, and discipline. Similarly, organizational culture also demonstrated a positive and significant effect on employee work effectiveness (β = 0.211; p = 0.038), suggesting that a supportive and collaborative culture fosters motivation, commitment, and efficiency in task completion. Together, these variables accounted for a substantial proportion of the variance in employee work effectiveness. The findings imply that strengthening leadership quality and embedding a constructive organizational culture are strategic priorities to improve service quality and operational efficiency in public sector institutions. This research contributes to the literature on public administration and human resource management by highlighting the integrated role of leadership and culture in enhancing work effectiveness within government service organizations.